Antifungal activity of microcapsule propolis from Tetragonula spp. to Candida albicans - Pratami, Diah Kartika; Indrawati, Teti; Istikomah, Iis; Farida, Siti; Pujianto, Paksi; Sahlan, Muhamad (Communications in Science and Technology, 2020)
Propolis is a mixture of resin and saliva of Tetragonula spp. that have antifungal activity. The purpose of this study was to develop spray-dried microcapsule propolis (SDMP) and to analyze its antifungal activity to Candida albicans. The SDMP was obtained using a spray drying method by maltodextrin and gum arabic coating. The antifungal activity of SDMP of rough propolis (taken from the outside beehive) and smooth propolis (taken from the inside beehive) was analyzed. The macroscopic characterization showed that SDMP has a powder form with brownish-yellow color. The microscopic characterization showed SDMP has a spherical uniform particle shape with particle size 9.32 - 14.61 µm. The encapsulation efficiency of smooth and rough SDMP was 81.22% and 83.04%; moisture content 5.58% and 5.84%; water solubility 98.19% and 98.31%, respectively. The microbial inhibitory concentration to C. albicans was the diameter of 6.33±1.5 to 10±2.5 mm. SDMP displayed remarkable activity in the assays against C. albicans.